2010
DOI: 10.1088/0004-637x/720/1/824
|View full text |Cite
|
Sign up to set email alerts
|

Can the Solar Wind Be Driven by Magnetic Reconnection in the Sun's Magnetic Carpet?

Abstract: The physical processes that heat the solar corona and accelerate the solar wind remain unknown after many years of study. Some have suggested that the wind is driven by waves and turbulence in open magnetic flux tubes, and others have suggested that plasma is injected into the open tubes by magnetic reconnection with closed loops. In order to test the latter idea, we developed Monte Carlo simulations of the photospheric "magnetic carpet" and extrapolated the time-varying coronal field. These models were constr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 155 publications
(265 reference statements)
2
82
1
1
Order By: Relevance
“…For example, it could be that the solar wind is heated by the dissipation of Alfvén waves whereas the solar corona is heated by magnetic reconnection events (Cranmer & van Ballegooijen 2010). Furthermore, Cohen (2011) pointed out that while the solar X-ray luminosity, L X , varies by over an order of magnitude during the solar cycle, the mass loss rate does not change in any significant way, and suggested therefore that the mass loss rates of other stars are independent of their X-ray properties.…”
Section: Scaling Base Temperaturementioning
confidence: 99%
“…For example, it could be that the solar wind is heated by the dissipation of Alfvén waves whereas the solar corona is heated by magnetic reconnection events (Cranmer & van Ballegooijen 2010). Furthermore, Cohen (2011) pointed out that while the solar X-ray luminosity, L X , varies by over an order of magnitude during the solar cycle, the mass loss rate does not change in any significant way, and suggested therefore that the mass loss rates of other stars are independent of their X-ray properties.…”
Section: Scaling Base Temperaturementioning
confidence: 99%
“…On the other hand, such interactions have been treated in local models "resolving" only a small portion of the solar surface. (Parnell 2001;Simon et al 2001;Rast 2003;Crouch et al 2007;Cranmer & van Ballegooijen 2010;Meyer et al 2011). These processes are highly non-linear, with smaller structures aggregating to form larger ones, and larger structures disintegrating into smaller ones, making models complex and computationally demanding.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of the small-scale coronal field, using either observed or synthetic magnetograms as the lower-boundary condition, include those of van Ballegooijen et al (1998), Schrijver & Title (2002), Close et al (2003), Close et al (2004), Parnell (2009), andvan Ballegooijen (2010). A limitation of the above studies is that they consider only potential magnetic fields and independent extrapolations of the coronal field for each magnetogram.…”
Section: Introductionmentioning
confidence: 99%